Distribution, relative abundance, and conservation status of Asian elephants in Karnataka, southern India. (July 2015) - Madhusudan, M.D.; Sharma, Narayan; Raghunath, R.; Baskaran, N.; Bipin, C.M.; Gubbi, Sanjay; Johnsingh, A.J.T.; Kulkarni, Jayant; Kumara, Honnavalli N.; Mehta, Prachi; Pillay, Rajeev; Sukumar, Raman
Highlights: We map the distribution and relative abundance of a key Asian elephant population. We describe ecological and anthropogenic characteristics of sites with elephants. Elephants are most abundant within protected areas, yet occur widely outside them. A fraught human–elephant interface pits elephant conservation against human well-being. Better conservation planning is essential for effective and enduring elephant conservation. Abstract: Karnataka state in southern India supports a globally significant—and the country's largest—population of the Asian elephant Elephas maximus . A reliable map of Asian elephant distribution and measures of spatial variation in their abundance, both vital needs for conservation and management action, are unavailable not only in Karnataka, but across its global range. Here, we use various data gathered between 2000 and 2015 to map the distribution of elephants in Karnataka at the scale of the smallest forest management unit, the 'beat', while also presenting data on elephant dung density for a subset of 'elephant beats.' Elephants occurred in 972 out of 2855 forest beats of Karnataka. Sixty percent of these 972 beats—and 55% of the forest habitat—lay outside notified protected areas (PAs), and included lands designated for agricultural production and human dwelling. While median elephant dung density inside protected areas was nearly thrice as much as outside, elephants routinely occurred in or used habitats outside PAs where human density, land fraction under cultivation, and the interface between human-dominated areas and forests were greater. Based on our data, it is clear that India's framework for elephant conservation—which legally protects the species wherever it occurs, but protects only some of its habitats—while being appropriate in furthering their conservation within PAs, seriously falters in situations where elephants reside in and/or seasonally use areas outside PAs. Attempts to further elephant conservation in production and dwelling areas have extracted high costs in human, elephant, material and monetary terms in Karnataka. In such settings, conservation planning exercises are necessary to determine where the needs of elephants—or humans—must take priority over the other, and to achieve that in a manner that is based not only on reliable scientific data but also on a process of public reasoning.